1996
DOI: 10.1161/01.atv.16.6.773
|View full text |Cite
|
Sign up to set email alerts
|

A Cytotoxic Electronegative LDL Subfraction Is Present in Human Plasma

Abstract: By using fast protein liquid chromatography, we isolated from human plasma a minor electronegative LDL subfraction designated LDL(-). After immunoaffinity chromatography against apolipoprotein (apo)(a) and apo A-I, LDL(-) represented 6.7 +/- 0.9% (mean +/- SD; n = 18) of total LDL. Compared with the major LDL subfraction, designated LDL(+), LDL(-) contained similar amounts of thiobarbituric acid-reactive substances, conjugated dienes, and vitamin E and had a similar lipid/protein ratio and mean density. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 54 publications
7
68
1
5
Order By: Relevance
“…Although some authors reported that LDL(Ϫ) contained increased oxidation products, 9,18,24 other investigators found no evidence of oxidative modification. 7,8,10 The high activity of PAF-AH in LDL(Ϫ) points to a possible role of this enzyme in the inflammatory effect of LDL(Ϫ). PAF-AH activity generates LPC and short-chain or oxidized NEFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some authors reported that LDL(Ϫ) contained increased oxidation products, 9,18,24 other investigators found no evidence of oxidative modification. 7,8,10 The high activity of PAF-AH in LDL(Ϫ) points to a possible role of this enzyme in the inflammatory effect of LDL(Ϫ). PAF-AH activity generates LPC and short-chain or oxidized NEFA.…”
Section: Discussionmentioning
confidence: 99%
“…6 Electronegative LDL [LDL(Ϫ)] is a subfraction of LDL present in plasma that induces the release of interleukin-8 and monocyte chemotactic protein-1 7,8 and is cytotoxic in cultured human endothelial cells. 9,10 The mechanism by which LDL(Ϫ) induces chemokine release remains unknown, although it could be related to some compositional differences compared with native LDL, with the most remarkable difference being an increased NEFA content in LDL(Ϫ) compared with native LDL. 7,8 The aim of the present work was to study whether the origin of increased NEFA in LDL(Ϫ) could be related to LDLassociated PLA 2 activity.…”
mentioning
confidence: 99%
“…39 However, recent data show that modification of LDL can occur in the blood. [13][14][15][16][17] Furthermore, prolonged LDL circulation times in the blood increase LDL's propensity to oxidation and may lead to LDL modification before it enters the artery wall. 40 Previous work from this laboratory showed that even short exposures to environmental tobacco smoke (4 hours) increased LDL accumulation in the artery wall.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recent studies demonstrate evidence of modification of LDL in the blood. [13][14][15][16][17] Furthermore, a previous study showed increased accumulation and degradation of oxidized LDL (OX-LDL) in the artery wall in vivo. 18 These studies suggest that the reason there is increased accumulation and degradation of OX-LDL is because arterial permeability to undegraded, OX-LDL is greater than arterial permeability to native LDL (N-LDL).…”
mentioning
confidence: 99%
“…lipid hydroperoxides and oxysterols [8]. It binds with diminished a¤nity to LDL receptors of human skin ¢broblasts and endothelial cells [9] but is a poor ligand for macrophage scavenger receptor [10]. In contrast to nLDL, LDL 3 is cytotoxic to cultured endothelial cells [11].…”
Section: Introductionmentioning
confidence: 99%